Using Reverse Genetics to Manipulate the NSs Gene of the Rift Valley Fever Virus MP-12 Strain to Improve Vaccine Safety and Efficacy - Kalveram, Birte (MyJove Corporation, 2011)
Rift Valley fever virus (RVFV), which causes hemorrhagic fever, neurological disorders or blindness in humans, and a high rate abortion and fetal malformation in ruminants(1), has been classified as a HHS/USDA overlap select agent and a risk group 3 pathogen. It belongs to the genus Phlebovirus in the family Bunyaviridae and is one of the most virulent members of this family. Several reverse genetics systems for the RVFV MP-12 vaccine strain(2,3) as well as wild-type RVFV strains (4-6), including ZH548 and ZH501, have been developed since 2006. The MP-12 strain (which is a risk group 2 pathogen and a non-select agent) is highly attenuated by several mutations in its M- and L-segments, but still carries virulent S-segment RNA(3), which encodes a functional virulence factor, NSs. The rMP12-C13type (C13type) carrying 69% in-frame deletion of NSs ORF lacks all the known NSs functions, while it replicates as efficient as does MP-12 in VeroE6 cells lacking type-I IFN. NSs induces a shut-off of host transcription including interferon (IFN)-beta mRNA(7,8) and promotes degradation of double-stranded RNA-dependent protein kinase (PKR) at the post-translational level.(9,10) IFN-beta is transcriptionally upregulated by interferon regulatory factor 3 (IRF-3), NF-kB and activator protein-1 (AP-1), and the binding of IFN-beta to IFN-alpha/beta receptor (IFNAR) stimulates the transcription of IFN-alpha genes or other interferon stimulated genes (ISGs)(11), which induces host antiviral activities, whereas host transcription suppression including IFN-beta gene by NSs prevents the gene upregulations of those ISGs in response to viral replication although IRF-3, NF-kB and activator protein-1 (AP-1) can be activated by RVFV7. . Thus, NSs is an excellent target to further attenuate MP-12, and to enhance host innate immune responses by abolishing the IFN-beta suppression function. Here, we describe a protocol for generating a recombinant MP-12 encoding mutated NSs, and provide an example of a screening method to identify NSs mutants lacking the function to suppress IFN-beta mRNA synthesis. In addition to its essential role in innate immunity, type-I IFN is important for the maturation of dendritic cells and the induction of an adaptive immune response(12-14). Thus, NSs mutants inducing type-I IFN are further attenuated, but at the same time are more efficient at stimulating host immune responses than wild-type MP-12, which makes them ideal candidates for vaccination approaches.